Philosophy of mathematics today - Agazzi, Evandro; Darvas, György (Springer, 1997)
The book is of interest to general philosophers of science, thanks to the attention paid to logical, linguistic and ontological issues regarding mathematics. People interested in foundational research will find penetrating papers regarding structuralist and set-theoretical approaches. Scientists may appreciate the analyses of the role of mathematics in several sciences